Modeling Dissolved and Particulate 230Th in the Canada Basin: Implications for Recent Changes in Particle Flux and Intermediate Circulation. Issue 2 (23rd February 2020) - Yu, Xiaoxin; Allen, Susan E.; François, Roger; Grenier, Mélanie; Myers, Paul G.; Hu, Xianmin
Abstract: Global climate change has had large impacts on the Arctic region including rapid reductions in sea ice and rapid increases in surface air temperatures. Documenting the consequences of these changes in the Arctic Ocean is difficult, however, because accessibility limits observations in space and time and aliases measurements. This problem can be alleviated by using geochemical tracers, which can act as natural integrators, allowing us to determine net changes over regions and years. One such tracer is 230 Th. We use measurements and an off‐line scavenging model forced by ANHA4, a regional configuration of the NEMO general circulation model, to investigate changes in the Canada Basin in the years 2002–2015. Observations show a clear decrease in 230 Th in intermediate layers, particularly in the internal Canada Basin. The model reproduces the observed changes in 230 Th concentration profiles. Using the model to determine the origin of the reduction shows that the decrease is due to both higher particle fluxes from increased productivity resulting from the reduction in sea ice cover and increased circulation and stirring by mesoscale eddies increasing lateral exchange between the productive coastal regions and less productive internal Canada Basin. The circulation model clearly shows increased velocities as the ice cover has decreased and storms have increased. Key Points: 230 Th concentration in Canada Basin has decreased due to enhanced productivity and due to increased exchange between margins and interior Including additional scavenging near the sea floor, the model better reproduces the observed 230 Th and its changes over the last two decades Use of 230 Th model, combined with observations, elucidates changes in the Arctic intermediate circulation